Two new fossil representatives of Eurypinae (Coleoptera: Tenebrionoidea: Mycteridae) from Eocene Baltic amber and placement of Neopolypria nigra Abdullah, 1964 - Alekseev, Vitalii I.; Pollock, Darren A.; Bukejs, Andris (Zootaxa, 2019)
Two new species of Eurypinae (Coleoptera: Mycteridae) are described from Eocene Baltic amber from the Kaliningrad Region, Russia: Glesoconomorphus nachzehrer gen. et sp. nov. and Omineus febribilis sp. nov. The first new fossil taxon displays affinity to recent members of the Neotropical Conomorphus-Stilpnonotus lineage, and the second species was placed into the present-day eastern and southeastern Asian genus Omineus Lewis. The fossil Neopolypria nigra Abdullah, 1964 (Baltic amber) is moved from Mycteridae and placed as incertae sedis within Tenebrionoidea Latreille, 1802.